Prediction of submarine scattered noise by the acoustic analogy. (21st July 2018) - Testa, C.; Greco, L.
Abstract: The prediction of the noise scattered by a submarine subject to the propeller tonal noise is here addressed through a non-standard frequency-domain formulation that extends the use of the acoustic analogy to scattering problems. A boundary element method yields the scattered pressure upon the hull surface by the solution of a boundary integral equation, whereas the noise radiated in the fluid domain is evaluated by the corresponding boundary integral representation. Propeller-induced incident pressure field on the scatterer is detected by combining an unsteady three-dimensional panel method with the Bernoulli equation. For each frequency of interest, numerical results concern with sound pressure levels upon the hull and in the flowfield. The validity of the results is established by a comparison with a time-marching hydrodynamic panel method that solves propeller and hull jointly. Within the framework of potential-flow hydrodynamics, it is found out that the scattering formulation herein proposed is appropriate to successfully capture noise magnitude and directivity both on the hull surface and in the flowfield, yielding a computationally efficient solution procedure that may be useful in preliminary design/multidisciplinary optimization applications. Highlights: A nonstandard frequency-domain scattering formulation is applied. It is suitable for the analysis of propeller tonal noise scattered by moving bodies. It allows a detailed view of submarine-propeller sound radiation mechanism. It is validated against numerical hydrodynamic results of the whole configuration. It is fast and accurate, thus useful for multidisciplinary/optimization purposes.